Non‐medical use of psychoactive prescription drugs is associated with fatal poisoning. (28th September 2017) - Haukka, Jari; Kriikku, Pirkko; Mariottini, Claudia; Partonen, Timo; Ojanperä, Ilkka
Abstract: Aims: The aims of this study were to estimate the prevalence and predictors of non‐medical substance use, and to assess the association between non‐medical substance use and fatal poisoning or history of drug abuse in Finland. Design and setting: Retrospective cohort study of all medico‐legally investigated death cases in Finland. The postmortem toxicology database was linked together with the register on reimbursed prescription medicines. Participants and cases: All postmortem cases between 2011 and 2013 positive for one or more of the following drugs: oxycodone, fentanyl, tramadol, clonazepam, gabapentin, pregabalin, tizanidine, olanzapine, quetiapine, risperidone, alprazolam, zolpidem, mirtazapine and bupropion, n  = 2974. Measurements: Non‐medical use of substance was the outcome variable. Predictors were the following: gender, residence at the time of death, place of death, blood alcohol concentration, age, drug abuse, number of prescriptions of any psychoactive drugs in last year and proportion of prescriptions issued by psychiatrist in last year. Findings: In 50.4% of the studied cases, at least one drug was detected without a prescription. Clonazepam, alprazolam and tramadol were the most prevalent non‐medical findings in these cases (6.6, 6.1 and 5.6%, respectively). The risk of non‐medical use of prescription drugs was especially high in cases with history of drug abuse (88.5%) and in fatal poisonings (71.0%). The proportion of non‐medical use of the studied substances varied between 5.9% [95% confidence interval (CI) = 3.1–10.1%)] for risperidone and 55.7% for fentanyl (95% CI = 44.1–66.9%). Valid prescription for one or more of any psychoactive drug was associated with lower odds for non‐medical use of the studied substances. Additionally, the higher the proportion of psychoactive drugs prescribed by a psychiatrist, the lower the probability of non‐medical use. Conclusions: Non‐prescribed psychoactive drugs are found commonly at postmortem in drug poisoning deaths in Finland, with history of drug abuse being a major contributing factor.